Análise genotípica e filogenética com base nos genes das glicoproteínas C e D de herpesvírus bovino 1 e 5 - Traesel, Carolina Kist (2013)
Bovine herpesviruses 1 (BoHV-1) and 5 (BoHV-5) are genetic and antigenic closely related pathogens of cattle, historically associated with respiratory/genital and neurological disease, respectively. This thesis reports the genomic and phylogenetic analyzes based on glycoproteins C (gC) and D (gD) genes of BoHV-1 and BoHV-5. Initially, the differentiation between BoHV-1 and BoHV-5 was performed by a differential PCR based on 5 gC gene. Then, a molecular analysis based on the 3 region of the gC gene of 45 BoHV isolates from Brazil, Uruguay and Argentina (1981-2009) was described. The phylogenetic tree reconstruction provided a clear distinction between BoHV-1 and BoHV-5, and BoHV-1 into subtypes BoHV-1.1 and BoHV-1.2. The levels of nucleotide (nt) similarity ranged from 99.1 to 100% among BoHV-1 sequences (n=12); 96.2-100% among BoHV-5 sequences (n=32); and 77.7-90.3% between BoHV-1 and BoHV-5 sequences. A transmembrane domain of 24 amino-acid (aa) and the putative cytoplasmic tail of 8 aa were also identified. In addition, a phylogenetic study was performed to investigate genetic divergences at the 3 region of gD gene of respiratory/genital BoHV-1 (n=7), neurological BoHV-1 (n=7) and neurological BoHV-5 (n=7) isolates, and whether these differences would be associated with the respective neurological presentation. The phylogenetic reconstruction allowed a clear differentiation of BoHV-1 (n=14) and BoHV-5 (n=7), but BoHV-1 isolates from neurological disease grouped within BoHV-1 branch. The nt and aa similarity levels were on average 98.3% among BoHV-1; 97.8% and 95.8% among BoHV-5; 73.7% and 64.1% between viral species. These results indicate that both genes revealed a high conserved 3 region within each species and a less conserved region between BoHV-1 and BoHV-5. The phylogenetic analyzes allowed differentiation of BoHV-1 and BoHV-5 species, and even subtypes grouped in distinct branches in the 3 gC gene-based study, indicating that this region represents a better choice for phylogenetic subgrouping. So, it was concluded that these genome regions represent a suitable target for phylogenetic classification of BoHV-1 and BoHV-5 isolates, and, perhaps, for understanding evolutionary relationships. However, no conclusion of a possible association of genetic differences with phenotypes could be drawn.